A new printed multiband fractal triangular antenna for wireless application - Mohamed Marzouk; Youssef Rhazi; Ibrahim Hassan Nejdi; Mohamed Saih (Universitas Ahmad Dahlan, 2024)
This letter investigates the properties of a novel multi-band fractal antenna with a triangular geometry that can expand its bandwidth, provide multiband functionality, and enable the best smart antenna technology. The antenna employs an FR4 as support with dimensions of 75x75 mm2 and a thickness of 1.6 mm. A microstrip line with an impedance of 50 ohms feeds the patch. The high-frequency structure simulator (HFSS) is applied to develop and simulate the patch. The vector network analyzer AVR ROHDE and SCHWARZ ZVB20 carried out the experimental tests of the prototype antenna. The suggested antenna's simulation results show that it runs on five main frequency bands: 1.840 GHz, 2.770 GHz, 2.940 GHz, 4.330 GHz, and 5.790 GHz, with a high gain that can exceed 6.01dB and an efficiency of 82%. In the operational bands, the voltage standing wave ratio (VSWR) is between one and two. The results from the simulation and the experiment are extremely similar.